The Relationships between Maturity and Functional Movement Screen Scores in School-Aged Girls and Boys - Khodayar Ghasempoor; Mohammad Hossein Alizadeh; Hooman Minoonejad; Mahdieh Akoochakian (Vesnu Publications, 2019)
Introduction: During the growth period, before and after maturity, considerable biological changes occur. It seems that these changes are related to neuromuscular patterns, and have significant differences in performing functional movements in young boys and girls during the maturation process. The purpose of this study was to examine the relationship between maturity and functional movement screen (FMS) scores in school-aged girls and boys. Materials and Methods: The statistical sample included 700 school-aged, 9-18-year-old, boys and girls from Shahrekord City, Iran, categorized into 10 groups of 35 girls and 10 groups of 35 boys. To evaluate maturity and functional movement, the maturity offset prediction equations and FMS tests were used, respectively. To investigate the relationship between maturity and FMS scores the Spearman's rank correlation coefficient test was used (P ≤ 0.050). Results: Spearman correlation test showed a significant correlation between maturity offset and FMS scores (r = 0.154, P < 0.001). Moreover, there was a significant correlation between maturity offset and FMS scores in boys (r = 0.334, P < 0.001), but this correlation was not significant in girls (r = -0.082, P > 0.050). Conclusion: There was a significant correlation between maturity and FMS scores in school-aged boys, but this correlation was not significant for girls. Therefore, realizing what changes may occur on the functional tests on the duration of the maturation process, can be considered as a goal for planning exercises; and some research can be done on the causes of these differences. Moreover, considering that functional tests may be affected by maturity, when interpreting these results, it is more accurate to consider biological age rather than chronological age.